527 Tumor organoid and immune cell co-culture system potentiates immuno-oncology drug development. (9th November 2020) - Zhang, Hongjuan; Zhou, Jun; Zhu, Shuang; Zheng, Jia; Shang, Limei; Li, Chunmei; Yan, Xuefei; Zhang, Rui; Zang, Mingfa; An, Annie Xiaoyu; Xu, Xiaoxi; Wang, Shuzong; et al.
Abstract : Background: Patient-derived organoids (PDOs) are derived from adult epithelial stem cell with self-renewal, organisation and differentiation properties, reflecting the original 3D organ-like or tissue-like structure and morphology in vitro. PDOs also faithfully recapitulate the genetic modifications and phenotypical features of original tumors, making them an attractive preclinical models for oncology drug development. However, modeling the tumor microenvironment (TME) in vitro remains a challenge due to the lack of stromal and immune cells. In this study, we reconstituted component of the TME through co-culture of tumor organoids with various immune cells in vitro to assess the immune modulatory and tumor killing effects of immuno-oncology (IO) drug candidates such as therapeutic monoclonal antibodies, bispecific T cell engagers and CAR-T cells. Methods: Using the Hubrecht organoid technology (HUB) protocols we have established a biobank of tumor and normal organoids, which closely resemble the genetic and morphologic features of original organs from multiple different tissue types. This large and diverse biobank of organoids can act as surrogates for individual patients making them suitable for patient population studies including evaluating the response to IO drug candidates in vitro. Results: We co-cultured organoids expressing tumor associated antigen (TAA) of interest with bispecific T cell engagers and CAR-T cells recognizing the TAAs. Our data demonstrated antigen-specific T cell killing of tumor organoids and tumor antigen reactivity of bispecific antibody activated T cells and CAR-T. We engineered tumor organoids to express CD19 and a luciferase reporter gene and measured luciferase activity to monitor the growth and killing of tumor organoids by CD19 CAR-T cells. The luciferase activity in organoids reflected the killing efficiency in a very sensitive, robust and high through-put manner. Immune checkpoint molecules are differentially expressed on individual tumor organoids and we evaluated the potency of immune check blockade using tumor organoids cocultured with allogenic T cells. Killing of tumor organoids and T cell activation was enhanced by PD-1/PD-L1 blockade. We profiled the expression of immune check point molecules on our banked tumor organoids which will provide a valuable resource to choose tumor models and cancer types for preclinical testing of IO drugs. Conclusions: In conclusion, we demonstrated the feasibility of in vitro patient-derived model system in the field of IO research using tumor organoid co-culture with immune cells, and their application in IO target and drug discovery.